PENYUSUNAN LAPORAN PENJUALAN SEDERHANA DI TAMAN WISATA GUDEM BEE FARM DESA SRI BINTAN - Hasnarika Hasnarika; Fazli Hadi Perwira; Indra Setiawan; Mell Yani; Putri Nadiah; Resdiawan Prabowo; Rizky Adhitya Putra (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
This study describes the community service program especially in the Gudem Bee Farm which is a tourist attractions in the KKN-P3M (Real – Center Work, Research and Community Service Lecture) activity in 2022 in Sri Bintan Village, Bintan District, Bintan Regency. The method used is observation, interview, documentation and training. The analysis carried out focuses on the problem in making the simple sales report. This analysis resulted in the resolution of the problem in the form of the program we were going to do namely making simple sales report to Gudem Bee Farm. With the method of solving the problem is expected to help solve the problem in Gudem Bee Farm.